Efficacy of Phytopharmaceuticals From the Amazonian Plant Libidibia ferrea for Wound Healing in Dogs - Américo, Ádria Vanessa Linhares dos Santos; Nunes, Kariane Mendes; Assis, Francisco Flávio Vieira de; Dias, Salatiel Ribeiro; Passos, Carla Tatiane Seixas; Morini, Adriana Caroprezo; Araújo, Junior Avelino de; Castro, Kelly Christina Ferreira; Silva, Silvia Katrine Rabelo da; Barata, Lauro Euclides Soares; Minervino, Antonio Humberto Hamad (Frontiers in Veterinary Science, 2020)
We comparatively evaluate two distinct formulations containing a 5% of Jucá (Libidibia ferrea) for wound healing in dogs. Excision model study was performed in eleven dogs with three dermal wounds in each animal, which were treated with: (1) topical gel formulated with 5% Jucá ethanolic extract and Carbopol base (PyC); (2) topical butter with 5% Jucá and murumuru fat base (PyM); (3) commercial ointment (control). Wound treatment was made in alternated days starting at day (D) one until D21. Macroscopic (all time-points) and histological (D0 and D21) analyses were performed. Antimicrobial The antimicrobial activity of Jucá was evaluated through Minimal Inhibitory Concentration (MIC). Phytochemical analysis of Jucá revealed 3.1% phenolic compound content expressed in rutin, and the presence of hydrolysable hydrolyzable tannins and flavonoids. The mean wound retraction was 33.7±5.5, 34.0±4.7, and 28.4±4.9 % for PyC, PyM and control groups, respectively, with higher wound retraction for both herbal-treated groups compared to control (P<0.05). Alcoholic extract of Jucá had antimicrobial activity against the microorganisms Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida krusei at different degrees with MIC ranging from 250 to 16.625 µg/ml. Microscopic evaluation showed that the phytotherapic formulations contributed to better dermal wound healing through wound fibroplasia. The alcoholic extract of Jucá pods has great potential for wound healing in dogs and can be used in the development of commercially viable phytotherapic formulations.